SELF-BRANDING STRATEGIES IN DIGITAL DA’WAH: A CASE STUDY OF GEN Z MUSLIM TIKTOK CREATOR @kadamsidik - Khairunnisa, Rahmahdalena Putri; Purmasari, Siti Fatimah; Surawan, Surawan (Bayan lin-Naas : Jurnal Dakwah Islam, 2025)
In the digital age, the internet and social media play a very important role in spreading religious teachings, especially for Generation Z. The rise of various digital platforms provides new opportunities for preachers to spread their messages online, especially to Generation Z teenagers. Social media, such as TikTok, which is currently very popular among Gen Z, not only serves as entertainment but also as a source of knowledge. This study aims to identify opportunities, challenges, and effective da'wah strategies through TikTok. The method used in this study is qualitative, involving literature review and analysis of content from the TikTok account @kadamsidik00. Data collection was conducted by observing creator videos and relevant literature. The findings show that social media provides broad access and creative tools for delivering da'wah messages. However, there are considerable challenges, such as distractions from non-religious content, the influence of secularism and materialism, and cultural diversity. Effective da'wah strategies include creating creative and interesting content that is in line with the preferences of Gen Z. The implications of this study emphasize the importance for Islamic preachers and organizations to adapt their da'wah methods to be more relevant to the digital culture and platforms used by the younger generation.